2021
DOI: 10.1002/cssc.202102132
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State C−N Cross‐Coupling Reactions with Carbazoles as Nitrogen Nucleophiles Using Mechanochemistry

Abstract: The palladium-catalyzed solid-state CÀ N cross-coupling of carbazoles with aryl halides via a high-temperature ball-milling technique has been reported. This reaction allowed simple, fast, and efficient synthesis of N-arylcarbazole derivatives in good to excellent yields without the use of large amounts of organic solvents in air. Importantly, the developed solid-state coupling approach enabled the cross-coupling of poorly soluble aryl halides with large polyaromatic structures that are barely reactive under c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…Notably, the strong mechanical agitation provided by ball milling enables efficient solid-state organic transformations. Thus far, mechanochemical palladiumcatalyzed cross-coupling reactions such as Suzuki-Miyaura [34][35][36][37][38][39][40][41][42][43][44][45][46][47], Buchwald-Hartwig [48][49][50][51][52], Sonogashira [53][54][55][56], Negishi [57], Mizoroki-Heck [58][59][60], and C-S bond-forming [61] reactions have been developed. Our group has also been interested in this class of mechanochemical transformations, particularly in the development of cross-coupling reactions that proceed in the solid state [43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the strong mechanical agitation provided by ball milling enables efficient solid-state organic transformations. Thus far, mechanochemical palladiumcatalyzed cross-coupling reactions such as Suzuki-Miyaura [34][35][36][37][38][39][40][41][42][43][44][45][46][47], Buchwald-Hartwig [48][49][50][51][52], Sonogashira [53][54][55][56], Negishi [57], Mizoroki-Heck [58][59][60], and C-S bond-forming [61] reactions have been developed. Our group has also been interested in this class of mechanochemical transformations, particularly in the development of cross-coupling reactions that proceed in the solid state [43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, mechanochemical palladiumcatalyzed cross-coupling reactions such as Suzuki-Miyaura [34][35][36][37][38][39][40][41][42][43][44][45][46][47], Buchwald-Hartwig [48][49][50][51][52], Sonogashira [53][54][55][56], Negishi [57], Mizoroki-Heck [58][59][60], and C-S bond-forming [61] reactions have been developed. Our group has also been interested in this class of mechanochemical transformations, particularly in the development of cross-coupling reactions that proceed in the solid state [43][44][45][46][47][48][49][50]. These mechanochemical cross-coupling reactions often show much faster reaction kinetics than those under conventional solution-based conditions because of the high concentration; further, the experimental operations can be carried out in air.…”
Section: Introductionmentioning
confidence: 99%
“… [17] In addition to the mainstream developments like amide synthesis,[ 18 , 19 , 20 , 21 , 22 , 23 ] the state‐of‐the‐art mechanochemical synthetic toolbox offers several opportunities to construct C−N bonds [24] in amines via alkylation[ 25 , 26 , 27 ] and arylation [28] with organic halides, including transition metal‐catalyzed couplings. [ 29 , 30 , 31 , 32 , 33 , 34 ] However, the use of alcohols as ubiquitous starting materials remains nearly untapped. [35] Nucleophilic substitution of the hydroxy group in alcohols is one of the most fundamental and widespread chemical transformations.…”
Section: Introductionmentioning
confidence: 99%
“…In light of these advantages, it is not surprising that mechanochemistry has been identified as one of the top 10 technologies that “will change our world,” and the field is a burgeoning area of research that may transform synthetic approaches to produce valuable molecules in drug, polymer, and functional material research. , Herein, we report the first mechanochemical solvent-free method for highly chemoselective synthesis of ketones from acyl chlorides and boronic acids (Figure B). Most importantly, this acylation reaction is conducted in the solid state, in the absence of potentially harmful solvents, for a short reaction time and shows excellent selectivity for C­(acyl)–Cl bond cleavage, including compatibility with various electrophilic functional groups. , Of general interest, Ito’s protocol for ball milling at high temperature has been successfully applied in challenging cases . We expect that this approach will facilitate the development of solid-state C­(acyl)-transfer reactions of widely available acyl electrophiles.…”
mentioning
confidence: 99%
“…This potentially powerful approach has a potential to provide a solution to the long-standing problem of solubility in solid-state mechanochemical synthesis. As such, we conducted select cross-couplings at higher preset temperatures according to Ito et al As shown in Scheme , this approach permits a marked increase in the reaction efficiency with the onset at 100 or 150 °C depending on the substrate class in this acyl coupling.…”
mentioning
confidence: 99%